Age‐Dependent Association between Heart Failure and Stroke Risk in Atrial Fibrillation: A Nationwide Cohort Study - Jalli, Eero; Langén, Ville; Jaakkola, Jussi; Airaksinen, K. E. Juhani; Halminen, Olli; Putaala, Jukka; Mustonen, Pirjo; Haukka, Jari; Hartikainen, Juha; Linna, Miika; Kouki, Elis; Lehto, Mika; et al. (Ovid Technologies (Wolters Kluwer Health), 2026)
Background
Atrial fibrillation (AF) is a major contributor to ischemic stroke, with risk influenced by age and comorbidities. Age is the strongest risk factor and appears to also modify others, such as vascular disease and female sex. However, data on its impact on additional key risk factors remain limited. We conducted a nationwide retrospective cohort study to examine whether the association between heart failure (HF) and ischemic stroke in patients with AF is age dependent.
Methods
The FinACAF (Finnish Anticoagulation in Atrial Fibrillation) study includes all patients with AF in Finland from 2007 to 2018. Data were collected from healthcare registries encompassing all levels of care. Incidence rate ratios for stroke were calculated comparing patients with HF to those without HF across the entire age spectrum.
Results
We identified 229 565 patients with new‐onset AF. The prevalence of HF was higher among older patients compared with younger patients (38.7% versus 4.3%, respectively). The association between HF and ischemic stroke was highest among younger patients (incidence rate ratio, ≥2.0 for those aged <60 years) and gradually diminished with advancing age, approaching an incidence rate ratio of ≈1.0 in the oldest group (P<0.001, for interaction between age and incidence rate ratio). The adjusted absolute rate difference between patients with and without HF remained stable, at ≈1 event per 100 patient‐years, across all age categories.
Conclusions
HF was more strongly associated with ischemic stroke in younger patients than in older individuals with AF, highlighting the importance of considering HF in the decision making about oral anticoagulation, particularly in younger patients.